Multiplex Detection of Biothreat Agents Using an Automated Electrochemical ELISA Platform. (2017) - Pöhlmann, Christopher; Bellanger, Laurent; Drevinek, Michal; Elßner, Thomas
Abstract: Modern threats of bioterrorism force the need to immediately identify biothreat agents. Here, we present an electrochemical detection platform for identification of six biothreat agents in parallel within approx. 20 minutes in an automated procedure. The detection platform is permanently housed in a robust, lightweight suitcase offering a fully deconable housing. Limits of detection are in the range of 10 3 - 10 5 colony forming units per mL or 10 4 - 10 5 plaque forming units per mL for bacterial or viral agents, respectively. These results demonstrate the potential of electrochemical biochips for parallel and sensitive on-site detection of biothreat agents.